(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
Since the triumph of the RPS on July 19, 1979, the U.S. has been determined to destroy it due to the immediate effect it caused in the region, an example that marked the possibilities for the peoples of Central America and the Caribbean to realize that the Puppet dictatorships of the north were not as unbeatable as we had been told. The U.S. interest was so marked that it distorted, manipulated the population and created the low-intensity war to stifle our revolution by destroying every advance in the economic, social and political field.